PENGARUH HARGA, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK ELFOS DHAF PADA TIKTOK SHOP DI INDONESIA - Rizqi Kamadianto; Subarjo (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine the effect of price, promotion, and product quality on purchasing decisions for Elfos Dhaf products at TikTok Shop in Indonesia. This study uses a questionnaire data collection method and probability sampling technique. The number of samples used was 100 respondents, which were obtained using the Lemeshow formula. The data analysis techniques used are descriptive analysis, multiple linear regression analysis, coefficient of determination test, and partial hypothesis test (t). The results showed that the price variable had a positive and significant effect on consumer purchasing decisions on Elfos Dhaf products, with a significance value of 0.029 (<0.05) and a t-count value of 2.213 (> t-table 1.664). The promotion variable is also proven to have a positive and significant effect on purchasing decisions, with a significance value of 0.013 (<0.05) and a t-count value of 3.019 (> t-table 1.664). However, the product quality variable has no significant effect on purchasing decisions, indicated by a significance value of 0.796 (>0.05) and a t-count of 0.259 (<t-table 1.664).